Українська самобутність у полеміці „малоросів” і росіян 70-90-х рр. ХІХ ст.: предметність критичних оцінок - Вишневська-Пилипишин, С. (Питання літературознавства, 2009)
Частково розглядається питання рецепції української літератури в російському суспільстві останньої третини ХІХ століття. Російські погляди на українське письменство подано за текстами й літературно-критичними оцінками того часу. Простежуються взаємовпливи в оцінках російськими та українськими критиками творчості І.П. Котляревського окресленого періоду. Taking for foundation the logic of judgments and considerations developed by Russian-soviet philosopher O.A. Ivin [4] in 60-70s of the 20th century, having learnt this logic towards literary criticism of R.T. Hromiak [3] we made an attempt of new treatise of I.P. Kotlirevskyi’s activity in Russian philology of the second part of the 19th century, that partially elucidates the problem of reception of Ukrainian literature in Russian society. The Russian works were considered in comparison with those ones of Ukrainian (Little Russian and Galician) publicists, taking to consideration the tendency to interference. Maintaining the geopolitics perspectives, Russians views on Ukrainian written language the researcher regenerates according with texts and literary, critical judgments of that time. In our opinion, the range of depicted fragments from media articles, critical essays displays the dynamics which was appurtenant to scientific consciousness of Russians in 70-90s of the 19th century.